Desensibilización con ciprofloxacina en una paciente con infección urinaria parcialmente tratada (2010)
ABSTRACT: Fluoroquinolones have been widely used for over 30 years and tolerance to them has been good. They are of broad spectrum against both gram positive and gram negative bacteria, although the activity of norfloxacin, ciprofloxacin and ofloxacin against streptococci and some anaerobic bacteria is rather limited. Their oral bioavailability is good and tissue penetration is adequate. Hipersensitivity reactions occur in about 1 per 50.000 treatments. We report a case of successful oral desensitization with ciprofloxacin in a patient with chronic partially treated urinary tract infection. This is the first desensitization with quinolones reported in Colombia.